ChemInform Abstract: Effect of Ester on Rhodium‐Catalyzed Intermolecular [5 + 2] Cycloaddition of 3‐Acyloxy‐1, 4‐enynes and Alkynes. Issue 27 (13th June 2013) - Schienebeck, Casi M.; Robichaux, Patrick J.; Li, Xiaoxun; Chen, Lianqing; Tang, Weiping
Abstract Significant rate acceleration is observed for the title reaction when acyloxy‐1, 4‐enynes (I) bearing a p‐dimethylaminobenzoate are employed as the 5‐carbon building block.